Phylogenetic relationships in Bulbostylis (Abildgaardieae: Cyperaceae) inferred from nuclear and plastid DNA sequence data - Reutemann Arnolfo, Andrea Guadalupe (2018)
Fil: Reutemann Arnolfo, Andrea Guadalupe. Universidad Nacional del Litoral. Facultad de Ciencias Agrarias; Argentina.